The Impact of Fiscal and Environmental Protection Budget on Ecological Protection and its Mechanism: – Based on Provincial Panel Data from 2014 to 2021 - Wang, Jiateng (Transactions on Economics, Business and Management Research, 2024)
This paper uses data from 30 provincial levels in China from 2014 to 2021 to empirically test the impact and mechanism of fiscal and environmental protection budgets on ecological protection. The results show that: (1) government budget expenditure has an enabling effect on ecological protection; (2) The comprehensive environmental situation plays a positive role in the fiscal and environmental protection budget to empower ecological protection; (3) The fiscal and environmental protection budgets of provinces in the eastern and central regions have a significant enabling effect on ecological protection, while the enabling role in the western region is weakened.